Parrhesia: The Development of the Meaning and Its Influence on the Christian Evangelization - Ishak Jacues Cavin; Klaus H. Raditio; Wahyu Santosa; Nikolas Kristiyanto (Fakultas Teologi, Universitas Sanata Dharma, 2024)
This study aims to display the development of the meaning of parrhesia Παρρησία which heavily influenced evangelization. Parrhesia is one of the most essential concepts in ancient Greek which added richness to the LXX and the New Testament. Parrhesia means eloquence, frankness, articulation and freedom of speech. In daily life, parrhesia is related to the expression of somebody’s mind (action de tout declarer, tout exprimer). Greek culture also denotes parrhesia as the political right to express somebody’s mind. The concept of parrhesia also contains the aspect of freedom in using the language. Indeed, the Hellenic root of parrhesia sets the course of the meaning of the word in the Scripture. This paper is divided into three parts to have a solid grasp of the meaning of parrhesia and its influence on evangelisation. The first elaborates on the development of the meaning of parrhesia using Foucauldian discourse analysis. The second explains how the word is used in Scriptural text (LXX and the New Testament). Finally, the scriptural meaning of parrhesia is perceived in the context of evangelization and the Church’s prophetic voices throughout history